U-Shaped Relationship of Low-Density Lipoprotein Cholesterol With Risk of Severe COVID-19 From a Multicenter Pooled Analysis - Gong, Jiao; Chen, Yaqiong; Jie, Yusheng; Tan, Mingkai; Jiang, Zhaofang; Yuan, Lianxiong; Cao, Jing; Li, Ganwen; Chong, Yutian; Qu, Jiuxin; Shi, Yaling; Hu, Bo (Frontiers in Cardiovascular Medicine, 2021)
Low-density lipoprotein cholesterol (LDL-C) is a well-known risk factor for coronary heart disease but protects against infection and sepsis. We aimed to disclose the exact association between LDL-C and severe 2019 novel coronavirus disease (COVID-19). Baseline data were retrospectively collected for 601 non-severe COVID-19 patients from two centers in Guangzhou and one center in Shenzhen, and patients on admission were medically observed for at least 15 days to determine the final outcome, including the non-severe group (n = 460) and the severe group (severe and critical cases) (n = 141). Among 601 cases, 76 (12.65%) received lipid-lowering therapy; the proportion of patients taking lipid-lowering drugs in the severe group was higher than that in the non-severe group (22.7 vs. 9.6%). We found a U-shaped association between LDL-C level and risk of severe COVID-19 using restricted cubic splines. Using univariate logistic regression analysis, odds ratios for severe COVID-19 for patients with LDL-C ≤1.6 mmol/L (61.9 mg/dL) and above 3.4 mmol/L (131.4 mg/dL) were 2.29 (95% confidence interval 1.12–4.68; p = 0.023) and 2.02 (1.04–3.94; p = 0.039), respectively, compared to those with LDL-C of 2.81–3.40 mmol/L (108.6–131.4 mg/dL); following multifactorial adjustment, odds ratios were 2.61 (1.07–6.37; p = 0.035) and 2.36 (1.09–5.14; p = 0.030). Similar results were yielded using 0.3 and 0.5 mmol/L categories of LDL-C and sensitivity analyses. Both low and high LDL-C levels were significantly associated with higher risk of severe COVID-19. Although our findings do not necessarily imply causality, they suggest that clinicians should pay more attention to lipid-lowering therapy in COVID-19 patients to improve clinical prognosis.